Implementasi Protokol 6LoWPAN Pada Purwarupa Wireless Sensor Nodes - Faisal Akhmadi; Sabriansyah Rizqika Akbar; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wireless Sensor Network appears as a network configuration that is able to provide solutions for a variety of applications in a difficult or unexpected situation. In general, there are two wireless communication standards used in WSN, namely IEEE 802.11 and IEEE 802.15.4. Each of these standards is able to present the use of Internet Protocol on WSN devices. The use of the IP protocol at WSN will bring the same benefits as IP on computer networks that have long been used, with various mechanisms and protocols that have been developed and used. In the absence of available blocks of IPv4 addresses, the use of IPv6 addresses must begin immediately. However, to bring IPv6 to WSN is hampered by limited resources. 6LoWPAN is here to enable the implementation of internet protocols to small devices. In this study, the design and implementation of wireless sensor prototypes using Raspberry Pi and MRF24J40MA as transceiver radio modules that use 6LoWPAN as the communication protocol is implemented. There are features added in this system that allow the sensor node to know the server's IP address without configuration. Also discussed about how to install MRF24J40MA so that it can be used for communication media using the 6LoWPAN protocol. The test results from this study indicate that overall, the system that has been made can run functionally and can use 6LoWPAN as a communication protocol.